The association between tyrosine kinase inhibitors and fatal arrhythmia in patients with non-small cell lung cancer in Taiwan - Chang, Wei-Ting; Lin, Hui-Wen; Chang, Ting-Chia; Lin, Sheng-Hsiang; Li, Yi-Heng (Frontiers in Oncology, 2023)
Objective: As a standard therapy, tyrosine kinase inhibitors (TKIs) improved survival in patients with non-small cell lung cancer (NSCLC) and epidermal growth factor receptor (EGFR) mutation. However, treatment-related cardiotoxicity, particularly arrhythmia, cannot be ignored. With the prevalence of EGFR mutations in Asian populations, the risk of arrhythmia among patients with NSCLC remains unclear. Methods: Using data from the Taiwanese National Health Insurance Research Database and National Cancer Registry, we identified patients with NSCLC from 2001 to 2014. Using Cox proportional hazards models, we analyzed outcomes of death and arrhythmia, including ventricular arrhythmia (VA), sudden cardiac death (SCD), and atrial fibrillation (AF). The follow-up duration was three years. Results: In total, 3876 patients with NSCLC treated with TKIs were matched to 3876 patients treated with platinum analogues. After adjusting for age, sex, comorbidities, and anticancer and cardiovascular therapies, patients receiving TKIs had a significantly lower risk of death (adjusted HR: 0.767; CI: 0.729–0.807, p < 0.001) than those receiving platinum analogues. Given that approximately 80% of the studied population reached the endpoint of mortality, we also adjusted for mortality as a competing risk. Notably, we observed significantly increased risks of both VA (adjusted sHR: 2.328; CI: 1.592–3.404, p < 0.001) and SCD (adjusted sHR: 1.316; CI: 1.041–1.663, p = 0.022) among TKI users compared with platinum analogue users. Conversely, the risk of AF was similar between the two groups. In the subgroup analysis, the increasing risk of VA/SCD persisted regardless of sex and most cardiovascular comorbidities. Conclusions: Collectively, we highlighted a higher risk of VA/SCD in TKI users than in patients receiving platinum analogues. Further research is needed to validate these findings.